KAJIAN PELAKSANAAN TUGAS DAN FUNGSI APRON MOVEMENT CONTROL (AMC) DI BANDAR UDARA INTERNASIONAL SOEKARNO – HATTA CENGKARENG TERHADAP KOMPETENSI LULUSAN OPERASI BANDAR UDARA (OBU) SEKOLAH TINGGI PENERBANGAN INDONESIA - Satiti Utami; Ir. Ika Endrawijaya (Langit Biru: Jurnal Ilmiah Aviasi, 2018)
The objective of research to know and inspect the task and function of Apron Movement Control (AMC) at Soekarno Hatta International Airport toword Competence at Airport Operation Gradate of Indonesia Civil Aviation Institute (ICAI). The method used is description analysis, with samples valve 86 respondents, through the questioner data collection techniques, the results of research that is in general the implementation at task and function of AMC units are less accordance with the Standard Operating Procedures either in terms of flight security and safety on the air side, shill infraction, that is in case disposition GSE exist shill in correct. However the result of this study can be improved that are socialiszation on periodic about regulation, SOP and also controlling and law inforcement.